Corpus-Assisted Creative Writing: Introducing Intermediate Italian Learners to a Corpus as a Reference Resource - Claire Kennedy; Tiziana Miceli (Language Learning and Technology)
In much of the literature on the exploitation of corpora for language learning, the learners are viewed as researchers, who formulate and test their own hypotheses about language use. Having identified difficulties encountered in corpus investigations by our intermediate-level students of Italian in a previous study, we have designed a semester-long apprenticeship in corpus use which does not demand of them the high level of language proficiency, attention to detail in observation, and logical rigour that we consider necessary for rewarding work in the learner-as-researcher role. Instead, we introduce a corpus initially as an aid to the imagination in writing, and then to achieving accuracy through specific grammatical problem solving. We see this as the groundwork for subsequent development of the students’ research skills with corpus data. This paper describes the approach we have adopted to the corpus apprenticeship and reports on an evaluation of its effectiveness through case studies of three students and their use of a corpus and bilingual dictionary as reference resources when writing. Drawing on insights from the case studies, we outline a working definition of corpus-consultation literacy for our learning context and identify some refinements to be made to our apprenticeship.